KEEFEKTIFAN MODEL PEMBELAJARAN COOPERATIVE LEARNING BERBANTUAN MEDIA KOMIK STRIP UNTUK MAHARAH KITABAH PADA SISWA KELAS VIII MTS NEGERI 2 KENDAL: THE EFFECTIVENESS OF A COOPERATIVE LEARNING MODEL ASSISTED WITH COMIC STRIP MEDIA TO IMPROVE STUDENTS' ARABIC WRITING SKILLS - Pradana, Muhammad Rif'an Alfudian Adi; Rahmawati, Nailur; Amrullah, Nafis (Universitas Negeri Semarang, 2024)
This research is based on the difficulties faced by MTs of state 2 Kendal students in learning Arabic writing skill, especially VIII-grade students. Among the difficulties they experience include remembering vocabulary, arranging sentences in the correct grammatical structure, and expressing ideas in written form. This difficulty is motivated by several factors, for example the characteristics of Arabic writing itself which are very different from Indonesian writing. Another factor is that students' levels of understanding vary due to their different educational backgrounds. The Cooperative Learning model assisted by comic strip media is present as one of the efforts offered as an alternative to this problem. The aim of this research is to describe the application of the Cooperative Learning model assisted by comic strip media for Arabic writing skill in VIII grade at MTs of state 2 Kendal students and analyze its effectiveness. The type of research in this study is quantitative research using a quasi-experimental research design with a non-equivalent control group design pattern. The data collection techniques used are test and non-test techniques. The results showed that the increase in the experimental class score from pre-test to post-test was greater than the control class. The average pre-test and post-test scores for the control class were 70,59 and 76,41. Meanwhile, the average pre-test and post-test scores for the experimental class were 73,59 and 84,64. Based on the t-test using SPSS, it is known that the significance value obtained is 0,007. Because 0,007 < 0,05 then H1 is accepted. Based on this statement, it can be concluded that